Life history of diabetics with injuries in feet: qualitative study - Moreira, Ricardo Castanho; Piassa, Maria de Freitas Lourenço; Silva, Flávia Teixeira Ribeiro; Haddad, Maria do Carmo Lourenço; Mantovani, Maria de Fátima (Online Brazilian Journal of Nursing, 2010)
The goal was to comprehend the life history of diabetic patients with foot ulcers. A qualitative research called life history was developed. The participants were people with foot ulcers from diabetes, with or without amputation, that were assisted by the Wounds Care Nusing Extension Project at the Northern Parana State University, in the city of Bandeirantes, from August 2009 to March 2010. Interviews were conducted in the participants’ home, after the Ethics on Research Committee. Data were analyzed through content analysis technique. Three men and one woman participated, and their speeches could be represented by two categories: discovery of diabetes and ways of management, and the perception of the diabetic foot and its daily repercussions. The benefits of this research is centered on the opportunity to comprehend this diabetes’ complication from the experience of those who live it.